Strengthening Democracy in Nepal: The Role of Trust, Transparency, and Anti-Corruption - Paudel, Keshav Raj; Phuyel, Shyam Prasad (Perspectives on Higher Education, 2025)
This study examines how trust, transparency, and anti-corruption measures contribute to strengthening political accountability in Nepal’s federal democratic system following the adoption of the 2015 Constitution. Nepal continues to grapple with governance issues, including unfulfilled political promises, weak leadership, limited transparency, and pervasive corruption—all of which have led to growing public distrust. The research aimed to assess how trust influences electoral participation, how transparency shapes public perception of accountability, and how anti-corruption measures can support ethical governance. Using a qualitative approach, the study gathered data from semi-structured interviews and focus groups involving political experts, party members, and civil society stakeholders. Results show that 60% of respondents distrust political parties, 75% view corruption as a major barrier, and transparency is seen as crucial by an equal share, particularly in decision-making. The study recommends adopting e-governance, empowering oversight institutions, and fostering ethical leadership to restore trust and improve political accountability.